EFEKTIVITAS PENERAPAN PERENCANAAN PULANG DENGAN METODE TERSTRUKTUR TERHADAP KESIAPAN KELUARGA DALAM MEMBERIKAN MOBILISASI DINI PADA PASIEN CEREBRO VASKULER ATTACK DI RS. ISLAM SURABAYA - Damawiyah, Siti; Ainiyah, Nur (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2017)
Discharge Planning in Surabaya Islamic Hospital done only when the patient will discharge in the form of discharge instructions. Providing health education to patients and families still incidental, which is given when the patient or his family have any question and it does not well prepared as a health education that suit with the patient's condition. This study uses quasy Experimental design, Control Group Pre Test – Post Test Design. Sample of this study are the family of stroke patients who were admitted in Surabaya Islamic Hospital with amount 30 respondents (15 respondents as treated group and 15 others as control group). Samples were taken by consecutive sampling technique. Statistically data analysis uses Mann Whitney test with a significance level 5% (0.05). Results of this study showed that the readiness of the treated group increased after a given structured discharge planning, from percentage value 0% to 53,33%. Results of statistically test by Mann Whitney got p value of readiness before and after giving structured discharge planning = 0.001 (p <0.05) means there is influence nursing in the treated group. Application of structured discharge planning increases readiness of families in caring for stroke patients in Surabaya Islamic Hospital. It is suggested in future studies to expand the study population and the discharge planning followed up until at home.